Primary Adrenal Insufficiency due to Cryptococcus With Persistent Adrenal Enlargement and Insufficiency - Catherine E. Price, MD; Cynthia Burns, MD; Joseph A. Aloi, MD (AACE Clinical Case Reports, 2023)
Background/Objective: Infiltrative fungal infections are an unusual cause of primary adrenal insufficiency (AI). Our objective is to present a long-term follow-up of a patient with AI due to cryptococcal adrenalitis. Case Report: A 47-year-old woman presented in January 2004, with 50-lb weight loss, nausea, emesis, and headache with diplopia. During the 6 months prior to her presentation the patient had multiple admissions for evaluation of recurrent nausea and emesis. Prior to the most recent of these admissions, the patient developed a headache; evaluation of her cerebrospinal fluid revealed the presence of Cryptococcus, and she was treated with a 2-week course of amphotericin B. Physical examination demonstrated a temperature of 101.1 °F, heart rate of 110 bpm, and blood pressure of 94/65 mm Hg. She appeared ill and was underweight with dry mucous membranes and photophobia. Laboratory tests revealed random cortisol of 0.5 μg per dL. CT imaging showed bilateral adrenal gland enlargement and fine needle aspiration of the adrenal gland revealed encapsulated budding yeast. Stress dose intravenous glucocorticoids were administered and switched to oral hydrocortisone and fludrocortisone because the patient clinically improved with a second course of amphotericin B. Further evaluation in 2017 revealed persistently enlarged adrenal glands, positive cryptococcus antigen, and low IgG levels. Discussion: Our literature review noted few publications of AI caused by disseminated cryptococcus with no long-term follow-up of these cases beyond a 1- to 4-year time frame. Conclusion: Patients with AI due to disseminated fungal infection need long-term follow-up to assess for resolution of adrenal enlargement and evaluation of immunocompromised status.